Pragmatic Transfer Analysis in Adjarra English Students’ Translation - LOKO, Djima Crépin; MOUSTAPHA-BABALOLA, Rissikatou; BABALOLA, Oba-Nsola Agnila Léonard Clément (My University, 2020)
This study examines the influence of pragmatic transfer on Adjarra English students’ translation. Translation assignments (Theme and Version) have been given to 15 students. Error analysis method is used by measuring and comparing the types and number of transfer with the translation methods used by the participants. The results show that the more students tend to translate word-for-word, or literally, it results in negative transfer; but when they use other methods of translation, the transfer is often positive. Also, the participants did more negative pragmatic transfer in theme than in version. This leads to conclude that the higher students’ linguistic proficiency is, the less negative pragmatic transfer happens.
Keywords: pragmatic transfer; translation; error analysis; language acquisition; linguistic proficiency.